educational intervention after medical intervention in developing language skills (Journal of the College of Basic Education, 2022)
Despite the great progress that has taken place in the field of phonetics, the science of language learning and the modification ofIts pronunciation can be corrected by drug treatment or by surgical intervention, but few have beenWhat he did in the field of medical and educational remedial training on pronouncing sounds and correcting deviant onesFor children who suffer from communication difficulties, and this is shown largely by finding specialists inThis field is in addition to the scarcity of research that deals with individuals who are unable to speak. As-Sahih (Arshad (1994).